O impacto socioeconômico na vida dos beneficiados do Programa Bolsa Família no município de Marechal Cândido Rondon – PR - Rodrigues, Marli Terezinha (2018)
The present study sought to analyze the impact that the Bolsa Família Program reflects on the lives of the beneficiaries from the municipality of Marechal Cândido Rondon. Identified the amounts paid for each benefit, it was possible to analyze how this income transfer program is understood and received by beneficiaries, considering the conditionalities, in the area of education and health as a form of social inclusion. It was verified that the objectives of the program to combat hunger and eradicate poverty were achieved both through quantitative data obtained through the website of the Ministry of Social Development and Fight against Hunger and through qualitative data obtained through the application of a questionnaire, where it was stated whether people are well informed about their rights and obligations and their role as a citizen and responsible for the human and social development of their family. Marechal Cândido Rondon currently has 455 beneficiary families of the Program, making a total of 1,783 people. The economic and social impacts on the lives of families receiving the benefit were verified, since they economically collaborate in the satisfaction of people's basic needs, especially in food, while conditionalities provide the obligatory access to education and health, later it is possible to think about social impact and can develop in the individuals critical thoughts and attitudes in search of satisfying their needs and rights as a citizen, in addition to redesigning a new socioeconomic scenario for the future generations, altering the generational cycle of the families and the society to which it is inserted.